Number agreement in Spanish spoken by Mapudungun-Spanish bilinguals. “Y después ya cambió eso cuando aprendió a hablar wingka los mapuche” - Olate Vinet, Aldo; Pineda Carrasco, Ricardo; Hasler Sandoval, Felipe; Soto Vergara, Guillermo (Círculo de Lingüística Aplicada a la Comunicación, 2019)
This paper studies the number disagreement in the noun phrase and the sentence level in the Spanish spoken by bilingual Mapudungun-Spanish speakers using the framework of the theory of language contact. The frequency of number disagreement in the sentence and the nominal phrase is determined from the analysis of a corpus of three thousand sentences produced by bilingual speakers from the territories of Lonquimay, Tranantue and Maquehue (The Araucania Region, Chile). The study shows that although the phenomenon has certain regularity, it is not predominant in the corpus. We propose that number disagreement could be explained as a code-copying from Mapudungun to Spanish by the bilingual speakers. Although more studies are necessary to confirm this hypothesis.
Keywords: Number Agreement in American Spanish; Language Contact; Mapuzugun-Spanish Interaction; Code Copy.